Tax litigation and the complexity of autonomous taxation of companies in Portugal - GIGANTE, Rita; DINIS, Ana; PEREIRA, Liliana (Revista Jurídica Portucalense, 2022)
This study focuses on the autonomous taxation of companies in Portugal (hereinafter AT), which is levied on certain corporate charges under the Corporate Income Tax Code (abbreviated as CITC). The AT has been the subject of constant litigation between the Tax Administration (hereinafter TA) and the companies, which reveals its complexity, and which justifies the relevance of this research. Through a study on the perception of chartered accountants (hereafter referred to as CA), to which a questionnaire survey was applied, and using a sample of 945 respondents, it was concluded that the CA respondents mostly consider that there is an excessive diversity of AT rates, as well as acknowledge that the AT rules require such an excessive preparation of accounting and tax information. The analysis also confirmed that as the experience of the CA respondents increases, so does their perception of legal disputes between taxpayers and the TA. Similarly, the results showed that as the number of companies for which the CA are responsible increases, the greater is their perception of the degree of difficulty in interpreting the AT rules.